PEREMPUAN DAN POLITIK, BUKAN SEKEDAR KUOTA 30% - Bintari, Antik (Bawaslu Provinsi Jawa Barat, 2022)
Women's political participation is an embodiment of the fulfillment of their citizenship rights. . Women as citizens and political entities have the right to improve their lives in the political sphere, so that women and other minority groups are not discriminated against. The tendency to give more space in the public sphere to men causes women not to have sufficient space in the ideas of statehood, including concerning the level of political participation. The research method carried out is descriptive research with data collection techniques with documentation studies. This paper aims to further analyze that the real issue of women and politics is not just the fulfillment of the 30% quota in parliament but how women can be involved in decision and policy making through various public spaces that open the widest possible access for women.In a such way, women can fully contribute to practical politics, especially with the holding of elections.